(untitled) (Studia Prawnicze / The Legal Studies, 2023)
Tekst prezentuje regulacje dotyczące kwestii, czy i kiedy podejrzany jest zobligowany do uczestniczenia w postępowaniach w przedmiocie zastosowania i przedłużania środka zabezpieczającego w postaci pobytu w zakładzie psychiatrycznym. Jeśli chodzi o postępowanie w przedmiocie zastosowania tego środka, to w szczególności rozważane jest zagadnienie, czy obecność podejrzanego pozostaje zawsze faktycznie obowiązkowa, jeśli biegli psychiatrzy stwierdzili w opinii, iż nie może on brać udziału w czynnościach lub, że jego udział w czynnościach jest niewskazany. Odnośnie zaś do postępowania wykonawczego, to postawione zostało pytanie, czy obecność osoby, wobec której stosowany jest taki środek, winna być obligatoryjna czy zależeć wyłącznie od jej woli. This paper presents regulations concerning the issue of whether and when the insane suspect is obliged to participate in proceedings concerning the application and extension of a precautionary measure in the form of a stay in a psychiatric institution. Regarding the procedure related to the application of this measure, the studied question is whether the presence of an insane suspect is in fact always obligatory if psychiatrists have stated that she cannot take part in the court activities or that her participation in these activities is inadvisable for her health. As for the enforcement proceedings, the main issue analyzed in this paper is whether the presence of the person against whom such a measure is applied should be always obligatory or should it depend solely on her will.